Inflation and capacity utilization in Nigeria’s manufacturing sector (2013)
This study analysed the relationship between inflation and capacity utilisation empirically leaning on the model employed by Baylor (2001). It utilised time series secondary data using least square multiple regression technique. The quarterly data utilised were tested for stationarity using ADF test. The multiple regression results showed a significant negative relationship between inflation and capacity utilisation. This finding was contrary to the economic argument which underpinned the intuition that the relationship between inflation and capacity utilisation should be positive. We also found that although the relationship between the two varied significantly over time, the model revealed that if current capacity utilisation rate doubled, inflation will decline by 3.6 per cent in Nigeria.